Amlodipine-induced lichenoid drug eruption: A case report (Bangladesh Journal of Medical Science, 2023)
Lichenoid drug eruption is a rare side effect which may occur following administration of several types of medication. The pathogenesis of lichenoid drug eruption is postulated to be due to persistent activation of CD8 T lymphocytes against epidermal cells. There were only a few cases of Amlodipine-induced lichenoid drug eruption reported in literature. Due to the rare occurrence, this disease might be overlooked and lead to delayed diagnosis and treatment. It is vital for the attending medical practitioner to be able to diagnose this disease as amlodipine was found to be the most utilised medication used in Malaysia according to the latest Malaysian Statistics on Medicine 2015-2016.We report a rare case of a 60-year-old Chinese gentleman who presented with predominant oral lesions as well as cutaneous lesions after initiation of amlodipine. A diagnosis of amlodipine-induced lichenoid drug eruption was made after thorough assessment and evaluation.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 229-233